2019
DOI: 10.1093/nar/gkz483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA motifs that regulate DNA methylation

Abstract: DNA methylation is an important epigenetic mark but how its locus-specificity is decided in relation to DNA sequence is not fully understood. Here, we have analyzed 34 diverse whole-genome bisulfite sequencing datasets in human and identified 313 motifs, including 92 and 221 associated with methylation (methylation motifs, MMs) and unmethylation (unmethylation motifs, UMs), respectively. The functionality of these motifs is supported by multiple lines of evidence. First, the methylation levels at the MM and UM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 100 publications
1
26
0
Order By: Relevance
“…It has been shown that GWAS SNVs systematically disrupt binding sites of TFs related to the traits ( 8 ), and that variation in TFBSs affects DNA binding, chromatin modification, transcription ( 9–11 ), and susceptibility to complex diseases ( 12 , 13 ) including cancer ( 14–17 ). In principle, variation in a CRM may result in changes in the affinity and interactions between TFs and cognate binding sites, thereby altering histone modifications and target gene expressions in relevant cells ( 18 , 19 ). Such alterations in molecular phenotypes can change cellular and organ-related phenotypes ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that GWAS SNVs systematically disrupt binding sites of TFs related to the traits ( 8 ), and that variation in TFBSs affects DNA binding, chromatin modification, transcription ( 9–11 ), and susceptibility to complex diseases ( 12 , 13 ) including cancer ( 14–17 ). In principle, variation in a CRM may result in changes in the affinity and interactions between TFs and cognate binding sites, thereby altering histone modifications and target gene expressions in relevant cells ( 18 , 19 ). Such alterations in molecular phenotypes can change cellular and organ-related phenotypes ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that complex trait-associated variants systematically disrupt TFBSs of TFs related to the traits (Maurano et al, 2012), and that variation in TFBSs affects DNA binding, chromatin modification, transcription(Kasowski et al, 2013; Kilpinen et al, 2013; McVicker et al, 2013), and susceptibility to complex diseases(Mathelier, Shi, & Wasserman, 2015; Smith & Shilatifard, 2014) including cancer(Herz, Hu, & Shilatifard, 2014; Khurana et al, 2016; Ongen et al, 2014; Zhou, Treloar, & Lupien, 2016). In principle, variation in a CRM may result in changes in the affinity and interactions between TFs and their binding sites, leading to alterations in histone modifications and target gene expressions in relevant cells(M. Wang et al, 2019; Whitaker, Chen, & Wang, 2015). These alterations in molecular phenotypes can lead to changes in cellular and organ-related phenotypes among individuals of a species(Pai, Pritchard, & Gilad, 2015; Ward & Kellis, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…al. 28 PSSMs are a commonly used tool in computational biology for the identification of motifs, in which the probability of each nucleotide in a subsequence is calculated in a position-dependent manner. Our software is designed to be modular, providing support for updated or different optimization requirements; users may provide their own PSSM matrices for sites to be avoided, providing greater customizability for unique engineering needs.…”
Section: Resultsmentioning
confidence: 99%